A rapid method for the simultaneous quantification of the major tocopherols, carotenoids, free and esterified sterols in canola (Brassica napus) oil using normal phase liquid chromatography. (1st January 2017) - Flakelar, Clare L.; Prenzler, Paul D.; Luckett, David J.; Howitt, Julia A.; Doran, Gregory
Highlights: New method developed for simultaneous analysis of bioactives in canola oil. Normal phase LC method suited to a non-polar sample matrix. APCI-MS/MS offers enhanced selectivity over previous methods. Minimal sample preparation and a short run time of 22 min. Individual free and bound sterols quantified, without need for saponification. Abstract: A normal phase high performance liquid chromatography (HPLC) method was developed to simultaneously quantify several prominent bioactive compounds in canola oil vis . α-tocopherol, γ-tocopherol, δ-tocopherol, β-carotene, lutein, β-sitosterol, campesterol and brassicasterol. The use of sequential diode array detection (DAD) and tandem mass spectrometry (MS/MS) allowed direct injection of oils, diluted in hexane without derivatisation or saponification, greatly reducing sample preparation time, and permitting the quantification of both free sterols and intact sterol esters. Further advantages over existing methods included increased analytical selectivity, and a chromatographic run time substantially less than other reported normal phase methods. The HPLC–DAD-MS/MS method was applied to freshly extracted canola oil samples as well as commercially available canola, palm fruit, sunflower and olive oils.